Targeted ferroptotic potency of ferrous oxide nanoparticles-diethyldithiocarbamate nanocomplex on the metastatic liver cancer - Abu-Serie, Marwa M. (Frontiers in Pharmacology, 2023)
Existing treatments are frequently ineffective in combating liver cancer (LC) due to its rapid growth, high metastatic potential, and chemoresistance. Thus, inducing ferroptosis, a new non-apoptotic regulated cell death-dependent massive iron overload-mediated lipid peroxidation, is an alternative effective approach for treating LC. The efficient trigger of ferroptosis requires blocking cellular antioxidant (anti-ferroptosis) response and selectivity to avoid harming other healthy tissues. In this study, green chemically synthesized ferrous oxide nanoparticles (F(II) NPs) were used for enhancing selective iron accumulation in tumor tissue, while diethyldithiocarbamate (DE) was for inhibiting the antioxidant system (glutathione and aldehyde dehydrogenase (ALDH) 2) which protects the tumor from damage-dependent lipid peroxides. Thus, F(II) NPs were used with DE as nanocomplex (DF(II) NPs) and its anti-LC activity compared to ferrous oxide DF(II). DF(II) NPs outperformed the typical complex of DF(II) in eradicating metastatic LC cells in HepG2 cells and a chemically induced metastatic LC animal model, as evidenced by flow cytometry, histological and immunohistochemical analyses, and α-fetoprotein depletion. The superior therapeutic potency-dependent ferroptotic activity of DF(II) NPs, attributed to their higher selective accumulation (~77%) than DF(II) in tumor tissues (liver and lung), resulted in a strong elevation of cellular lipid peroxidation with extreme suppression of nuclear related factor 2 (Nrf2) transcriptional activity, glutathione (GSH), glutathione peroxidase 4, and ALDH2. Subsequently, a severe inhibition in the expression of oncogenes and metastatic cancer stem cell genes was recorded in DF(II) NPs-treated LC animal group. In contrast to DF(II), DF(II) NPs were able to normalize liver functions and did not show any variations in hematological and histological parameters in the blood and tissues of DF(II) NPs-treated normal mouse group. These findings validate the potency and safety of DF(II) nanocomplex as a promising nanodrug for combating metastatic LC.